On the principles of a note circulation - Murphy, Joseph John (Dublin Statistical Society, 1857)
It may be regarded as established beyond controversy, that the convertibility of bank notes must be preserved. But the conditions under which convertible notes ought to be issued are still open to discussion. Dr Hancock maintains, in his defence of the Bank Charter Act of 1844, that notes being, like coin, part of the circulating medium, they ought, like coin, to be issued by the state or under its immediate care. I agree with this argument in so far as it is consistent >n itself. I think that the state ought to be the issuer of the paper circulation, in the same sense that it is the issuer of the metallic circulation. But the expression, "issuer of the circulation," is ambiguous. The state issues the metallic circulation in the sense of stamping it, in order to authenticate its value ? not in the sense of supplying the country with a metallic currency.
Read May 18th, 1857
Keywords: Currency; Bank notes; 314.15